Strategi Pengembangan Usaha Mikro Perempuan dalam Meningkatkan Kesejahteraan Ekonomi Keluarga (Studi Kasus di Desa Sabungan Sumatera Utara) - Siregar, Arnisah; Hidayat, Faisal; Febrian, Andis; Rais, Muhammad (Universitas Islam Lamongan, 2025)
This study aims to answer the question of what strategies are used in developing women's microbusinesses in Sabungan, North Sumatera to improve family economic well-being. This study is a descriptive qualitative study. Data were obtained through observation, interviews, document studies, and documentation. The results of this study indicate that the strategy for developing women's microbusinesses in Sabungan plays an important role in improving family economic welfare by developing the market in terms of products and sales systems as well as developing networks. The use of technology and Islamic financial institutions also plays an important role in increasing access to capital and profits. By implementing this strategy, microbusiness actors can increase competitiveness, expand market access, and improve family economics so that they become more prosperous. An effective assistance strategy to improve knowledge and management skills is through regular assistance programs such as basic financial recording training and support from financial institutions or cooperatives, accompanied by monitoring and evaluation. With the right assistance strategy, Sabungan entrepreneurs strengthen the competitiveness of women's businesses and contribute to improving the economic welfare of families.